(untitled) (Eurasian Research Bulletin, 2023)
The article describes the theoretical issues of the formalization of the results of the chamber tax audit. The effectiveness of the cameral tax audit depends on the level of formalization of its results. The increase in the effectiveness of the cameral tax audit is related to the fact that the auditor conducts a pre-audit analysis before the cameral tax audit begins.